(untitled) (Damascus University Journal of Historical Studies, 2023)
Belgium strived upon its independence in 1245 AH / 1830 AD to expand its commercial business outside its borders, and with the outbreak of the industrial revolution in its lands, the need for this expansion appeared to secure raw materials for its factories and then a market for the disposal of its industrial products. The Ottoman Sultanate during the years 1254-1255 AH / 1839-1840 AD, thus opening the commercial doors of the Sultanate to it, and then Belgium followed the approach of the capitalist European countries by exploiting the political, economic, social, and cultural crises that the Sultanate was going through to contribute to providing loans to it along with other European countries. Then it began exporting its capital to the Sultanate little by little to start its investments there. It obtained several investments in Thessaloniki, Izmir, and Istanbul, in addition to contributing several other investments with European countries investing there. Which helped Belgium to achieve huge profits to supplement its economy; However, she was not very lucky, and she was not able to single out many investments; Because it was unable to stand up to the major European countries, Belgium’s investments remained few compared to the investments obtained by other European countries (Britain - France - Germany) in the Ottoman Sultanate.